Fundamentals of the Thermohydrogravidynamic Theory of the Global Seismotectonic Activity of the Earth. (24th June 2013) - Simonenko, Sergey V.
Abstract : The article presents the fundamentals of the cosmic geophysics (representing the deterministic thermohydrogravidynamic theory intended for earthquakes prediction) based on the author's generalized differential formulation of the first law of thermodynamics extending the classical Gibbs' formulation by taking into account (along with the classical infinitesimal change of heatδ Q and the classical infinitesimal change of the internal energydU τ ) the infinitesimal increment of the macroscopic kinetic energydK τ, the infinitesimal increment of the gravitational potential energyd π τ, the generalized expression for the infinitesimal workδ A np, ∂ τ done by the nonpotential terrestrial stress forces (determined by the symmetric stress tensorT ) acting on the boundary of the continuum regionτ, and the infinitesimal incrementdG of energy due to the cosmic and terrestrial nonstationary energy gravitational influence on the continuum regionτ during the infinitesimal timedt . Based on the established generalized differential formulation of the first law of thermodynamics, the author explains the founded cosmic energy gravitational genesis of the strong Chinese 2008 and the strong Japanese 2011 earthquakes.